Silane polymer and modified acrylate pressure-sensitive adhesive thereof

By controlling the polymerization degree and proportion of silane polymer and chemically grafting with acrylate pressure-sensitive adhesive, the existing silane-modified acrylate pressure-sensitive adhesive is solved, and the problem of hydrolysis, polycondensation and crosslinking reactions are easily caused under high temperature and high humidity conditions, achieving efficient bonding and weather resistance of the modified acrylate pressure-sensitive adhesive.

CN119751495AActive Publication Date: 2025-04-04SUZHOU SHIHUA NEW MATERIAL TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202412000471.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Existing silane-modified acrylate pressure-sensitive adhesives are prone to hydrolysis, polycondensation, and cross-linking reactions under high temperature and high humidity conditions, resulting in gel, explosive polymerization and other conditions during the reaction, affecting its adhesive properties and weather resistance.

Method used

By controlling the polymerization degree and silane ratio of the silane polymer, a silane polymer with a polymerization degree of 2-6 was prepared, and chemically grafted with the acrylate pressure-sensitive adhesive to form a modified acrylate pressure-sensitive adhesive. This method improves the weather resistance and adhesion properties of the glue by adjusting the hydrolysis rate and peel force climb rate of the silane polymer.

Benefits of technology

The stability and weather resistance of acrylate pressure-sensitive adhesives under high temperature and high humidity conditions are achieved, ensuring short-term reworkable and long-term durable adhesive properties in high-end electronic products or optical components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005229606770000091
    Figure BDA0005229606770000091
Patent Text Reader

Abstract

The invention relates to the technical field of acrylate pressure-sensitive adhesives, in particular to a silane polymer and a modified acrylate pressure-sensitive adhesive thereof.The silane polymer is prepared through a hydrolytic condensation reaction of a functional silane monomer and an alkoxy silane monomer in a first solvent according to the molar ratio of 2: 1-1: 3 under the action of a catalyst water-alcohol solution; the polymerization degree of the silane polymer is 2-6; when the silane polymer modified acrylate pressure-sensitive adhesive is applied to high-end electronic products or optical components, short-time reworking, durable bonding performance and weather resistance are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of acrylic ester pressure-sensitive adhesives, in particular to a silane polymer and an acrylic ester pressure-sensitive adhesive modified therefrom. Background Art

[0002] With the development of acrylic pressure-sensitive adhesive, from the initial use in the field of tape labels, to the use of acrylic pressure-sensitive adhesive in more and more fields, such as consumer electronics, optical components and other fields. At the same time, higher requirements are also put forward for it. Due to the thermoplasticity of acrylic resin itself and the lack of cross-linking points on the linear molecules, its high temperature resistance is poor, and it lacks elasticity at low temperatures and is easy to become brittle; while organic silane has good heat resistance and weather resistance, so some scholars use silane to modify it.

[0003] There are two common ways to modify acrylic resin by silane:

[0004] One is physical blending, which is prone to phase separation and has a short storage period. Moreover, before use, most of the silicone active groups have been polymerized and there is no chemical bonding between the acrylic polymer and the substrate, which greatly reduces its weather resistance and adhesion.

[0005] The second method is to graft silane onto acrylic polymer by chemical copolymerization, such as using monomer silanes such as methacryloxytriethoxysilane and vinyltriethoxysilane for chemical copolymerization. Since silane monomers are highly active, they are prone to hydrolysis, condensation, and cross-linking reactions under high temperature and high humidity conditions, which can lead to gelation and violent polymerization during the reaction. In addition, monomer silanes have a small molecular weight and are easily volatilized under high temperature conditions, resulting in loss of input and making them difficult to measure.

[0006] Silane-modified acrylate pressure-sensitive adhesive is used in high-end electronic products or optical components. In order to prevent expensive electronic components and optical components from being unable to be reused due to inaccurate initial bonding of the pressure-sensitive adhesive, the pressure-sensitive adhesive needs to have short-term reworkability. After accurate bonding, it is hoped that the pressure-sensitive adhesive will firmly adhere to the adherend, and at this time the pressure-sensitive adhesive needs to have long-lasting and durable bonding properties.

[0007] Therefore, it is necessary to develop new technical means to make the pressure-sensitive adhesive have short-term reworkability, long-term durable bonding properties and good weather resistance and adhesion. Summary of the invention

[0008] The purpose of the present invention is to develop a silane polymer for use in an acrylic pressure-sensitive adhesive. By controlling the degree of polymerization and the silane ratio of the silane polymer, the modified acrylic pressure-sensitive adhesive can achieve short-time rework, durable adhesion and weather resistance when used in high-end electronic products or optical components.

[0009] Solutions for solving technical problems

[0010] The first aspect of the present invention provides a silane polymer, which is prepared by hydrolysis and condensation reaction of a functional silane monomer and an alkoxysilane monomer in a solvent at a molar ratio of 2:1 to 1:3 under the action of a catalyst water-alcohol solution, and the polymerization degree of the silane polymer is 2-6; the functional silane monomer is one or more of vinyl silane, mercapto silane, acyloxy silane, and epoxy silane, and the alkoxy silane monomer is an alkyltrialkoxysilane or / and a tetraalkoxysilane with different alkyl chain lengths.

[0011] The degree of polymerization of the silane polymer is limited to 2-6. The hydrolysis rate of silane polymer is slower than that of silane monomer, and volatile gases such as alcohols will not be produced in large quantities in a short time, thereby effectively reducing polarizer defects caused by bubble generation. Therefore, silane polymer has better weather resistance than silane monomer. By controlling the degree of polymerization, the climbing rate of the peeling force can also be controlled. If the degree of polymerization is less than 2, the climbing rate is too fast and affects the reworkability. If the degree of polymerization is greater than 6, the rate of increasing the peeling force is too slow, which is prone to bonding problems.

[0012] The molar ratio of the functional silane monomer to the alkoxysilane monomer (hereinafter referred to as the silane ratio) is set to 2:1 to 1:3, so as to control the peel force climbing rate by controlling the ratio of the functional silane monomer with different hydrolysis rates to the alkoxysilane monomer.

[0013] Preferably, the functional silane monomer is one or more of vinyltrimethoxysilane, vinyltriethoxysilane, mercaptopropyltrimethoxysilane, mercaptopropyltriethoxysilane, methacryloxytrimethoxysilane, methacryloxytriethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, thiocyanatopropyltrimethoxysilane, and thiocyanatopropyltriethoxysilane.

[0014] Preferably, the alkoxysilane monomer is one or more of methyltrimethoxysilane, methyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, tetramethoxysilane, tetraethoxysilane and tetrapropoxysilane.

[0015] Preferably, the catalyst is one or more of hydrochloric acid, nitric acid, sulfuric acid, acetic acid, trifluoromethanesulfonic acid, oxalic acid, and dodecylbenzenesulfonic acid.

[0016] Preferably, the solvent is selected from one or more of methanol, ethanol, isopropanol, pentanol and octanol.

[0017] A second aspect of the present invention provides a method for preparing a silane polymer, comprising the following steps:

[0018] S1: adding a catalyst to a hydroalcoholic solution and adjusting the pH to acidic to obtain a catalyst hydroalcoholic solution;

[0019] S2: under nitrogen protection, functional silane monomer, alkoxysilane monomer and solvent are added into the reactor in proportion and mixed, and the oil bath is heated;

[0020] S3: adding the catalyst aqueous alcohol solution obtained in step S1 dropwise into the reactor to carry out a hydrolysis condensation reaction to obtain a silane polymer.

[0021] Preferably, in step S1, the weight ratio of water to alcohol is 1:1-1:3, and the pH value of the catalyst aqueous alcohol solution is 2-6.

[0022] Preferably, in the step S2, the amount of solvent 1 added is 0.3-2 times of the total amount of the material, and the oil bath is heated to 40-50°C.

[0023] Preferably, after the catalyst aqueous alcohol solution is added dropwise in step S3, the temperature is first kept warm and then slowly raised to 75-110° C.; the hydrolysis condensation reaction is carried out while removing the solvent.

[0024] Preferably, the amount of the catalyst aqueous alcohol solution added in step S3 is such that the degree of polymerization of the silane polymer is 2-6.

[0025] In a third aspect, a silane polymer modified acrylate pressure-sensitive adhesive is characterized in that after (meth)acrylate monomers and (meth)acrylic acid functional monomers in solvent 2 are initiated by a thermal initiator, a silane polymer is added and reacted to obtain the adhesive.

[0026] Preferably, the (meth)acrylate monomer is a (meth)acrylate alkyl ester containing 1 to 12 carbon atoms, and the content of the (meth)acrylate monomer is 60 to 100 parts by weight, for example, 60 parts by weight, 70 parts by weight, 80 parts by weight, 90 parts by weight, 100 parts by weight, and any range between any two values.

[0027] Further preferably, the (meth)acrylate monomer is an alkyl (meth)acrylate containing 4 to 12 carbon atoms, including butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, ethyl (meth)acrylate, methyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, etc., and these can be used alone or in combination of two or more.

[0028] Preferably, the (meth)acrylic acid functional monomer is a monomer containing a hydroxyl functional group or a carboxyl functional group that reacts with a silane polymer. The content of the (meth)acrylic acid functional monomer is 0.2 to 4 parts by weight, for example, 0.2 parts by weight, 0.4 parts by weight, 0.6 parts by weight, 0.8 parts by weight, 1.6 parts by weight, 2 parts by weight, 2.6 parts by weight, 3 parts by weight, 3.6 parts by weight, 4 parts by weight, and any range between any two values.

[0029] Further preferably, the (meth)acrylic acid functional monomer includes monomers containing hydroxyl groups such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, diethylene glycol mono(meth)acrylate, and dipropylene glycol mono(meth)acrylate, and monomers containing carboxyl groups such as (meth)acrylic acid, (meth)acrylic acid dimer, itaconic acid, maleic acid, and maleic anhydride, and these can be used alone or in combination of two or more.

[0030] Preferably, the thermal initiator is one or more of azobisisobutyronitrile, benzoyl peroxide, dibenzoyl peroxide, and di-tert-butyl peroxide. The content of the thermal initiator is 0.01-0.5 parts by weight, such as 0.01 parts by weight, 0.05 parts by weight, 0.1 parts by weight, 0.3 parts by weight, 0.5 parts by weight, and any range between any two values.

[0031] Preferably, the solvent 2 is one or more of ethyl acetate, methyl ethyl ketone, methyl ether, toluene, xylene, cyclohexane, hexane, and octane. The content of the solvent 2 is 80-150 parts by weight, such as 80 parts by weight, 90 parts by weight, 100 parts by weight, 120 parts by weight, 140 parts by weight, 150 parts by weight, and any range between any two values.

[0032] Preferably, the content of the silane polymer is 0.1-2 parts by weight, for example 0.1 parts by weight, 0.2 parts by weight, 0.35 parts by weight, 0.55 parts by weight, 0.85 parts by weight, 1.25 parts by weight, 1.75 parts by weight, and any range between any two values.

[0033] The fourth invention of the present invention provides a method for preparing a silane polymer modified acrylic pressure-sensitive adhesive, which specifically comprises the following steps:

[0034] Add (meth)acrylate monomer, (meth)acrylic acid functional monomer and solvent 2 into a reaction kettle, heat to 55-75°C, add a thermal initiator, and after initiation, slowly add a silane polymer solution, control the addition time to 30-60 minutes, and continue to react after addition to obtain a silane polymer modified acrylate pressure-sensitive adhesive.

[0035] A fifth aspect of the present invention provides application of silane polymer modified acrylate pressure sensitive adhesive in 3C electronic product screens.

[0036] Beneficial effects of the present invention:

[0037] 1. Silane polymer is polymerized by functional silane monomer and trialkoxysilane and / or tetraalkoxysilane, and the functional groups on the functional silane monomer react and graft with the functional groups on the acrylic resin; due to the low surface tension of the silane polymer, its introduction can appropriately reduce the initial viscosity of the acrylic resin and give the acrylic pressure-sensitive adhesive short-term reworkability.

[0038] 2. The introduction of silane polymer can reduce the initial peel force to between 400-600. When rework is required, the substrate can be easily torn off without residual glue or damage to the substrate, thus not affecting the reuse of the optical substrate. The degree of polymerization of the silane polymer is limited to 2-6, making it difficult for the silane polymer to hydrolyze. The methanol and ethanol produced by the hydrolysis of silane are reduced, thereby achieving the effect of inhibiting the generation of bubbles and improving weather resistance.

[0039] 3. Compared with silane monomers, silane polymers have better stability under high temperature and high humidity conditions, and after being grafted onto acrylic resins, they also give acrylic resins good weather resistance. After the acrylic pressure-sensitive adhesive is bonded, during the long-term bonding process, the alkoxy groups in the silane polymers will slowly hydrolyze into silanol groups, combining with the hydroxyl groups on the surface of the optical material, giving the acrylic pressure-sensitive adhesive long-lasting and durable bonding properties. DETAILED DESCRIPTION

[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Synthesis example

[0042] Silane polymer 1 (degree of polymerization is 2)

[0043] Under nitrogen protection, add 74g of vinyltrimethoxysilane, 82g of propyltrimethoxysilane and 46.8g of methanol to a three-necked flask, stir well and heat to 45°C; mix 9g of water with 18g of methanol, add 30% hydrochloric acid to adjust the pH to 3, then add to a constant pressure dropping funnel and drip, drip in about 4 hours, keep warm for 0.5 hours after dripping, then heat to 85°C and reflux for 2 hours, then slowly collect alcohol for 5 hours, keep warm for 1 hour after alcohol collection is completed, and end the reaction. Collect for later use.

[0044] Silane polymer 2 (degree of polymerization 3)

[0045] Under nitrogen protection, add 164g of methacryloxypropyltrimethoxysilane, 54g of propyltrimethoxysilane, and 65.4g of methanol to a three-necked flask, stir well and heat to 45°C, mix 12g of water with 24g of methanol, add 30% hydrochloric acid to adjust the pH to 3, then add to a constant pressure dropping funnel and drip, drip in about 4 hours, keep warm for 0.5 hours after dripping, then heat to 85°C and reflux for 2 hours, then slowly collect alcohol for 5 hours, keep warm for 1 hour after the alcohol is collected, and end the reaction. Collect for use.

[0046] Silane polymer 3 (degree of polymerization 6)

[0047] Under nitrogen protection, add 59g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 156g of tetraethoxysilane, and 64.5g of methanol to a three-necked flask, stir well and heat to 45°C, mix 14.9g of water with 30g of methanol, add 30% hydrochloric acid to adjust the pH to 3, then add to a constant pressure dropping funnel and drip, drip in about 4 hours, keep warm for 0.5 hours after dripping, then heat to 85°C and reflux for 2 hours, then slowly collect alcohol for 5 hours, keep warm for 1 hour after alcohol collection is completed, and end the reaction. Collect for use.

[0048] Silane polymer 4 (degree of polymerization 1.5)

[0049] Under nitrogen protection, add 74g of vinyltrimethoxysilane, 82g of propyltrimethoxysilane, and 46.8g of methanol to a three-necked flask, stir well and heat to 45°C, mix 6g of water with 12g of methanol, add 30% hydrochloric acid to adjust the pH to 3, then add to a constant pressure dropping funnel and drip, drip in about 4 hours, keep warm for 0.5 hours after dripping, then heat to 85°C and reflux for 2 hours, then slowly collect alcohol for 5 hours, keep warm for 1 hour after alcohol collection is completed, and end the reaction. Collect for later use.

[0050] Silane polymer 5 (degree of polymerization 8)

[0051] Under nitrogen protection, add 59g of Y-(2,3-epoxypropoxy)propyltrimethoxysilane, 156g of tetraethoxysilane, and 64.5g of methanol to a three-necked flask, stir well and heat to 45°C, mix 15.75g of water with 32g of methanol, add 30% hydrochloric acid to adjust the pH to 3, then add to a constant pressure dropping funnel and drip, drip in about 4 hours, keep warm for 0.5 hours after dripping, then heat to 85°C and reflux for 2 hours, then slowly collect alcohol for 5 hours, keep warm for 1 hour after alcohol collection is completed, and end the reaction. Collect for later use.

[0052] Silane polymer 6 (degree of polymerization 6)

[0053] Under nitrogen protection, add 39g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 173g of tetraethoxysilane, and 63.6g of methanol to a three-necked flask, stir well and heat to 45°C, mix 14.9g of water with 30g of methanol, add 30% hydrochloric acid to adjust the pH to 3, then add to a constant pressure dropping funnel and drip, drip in about 4 hours, keep warm for 0.5 hours after dripping, then heat to 85°C and reflux for 2 hours, then slowly collect alcohol for 5 hours, keep warm for 1 hour after alcohol collection is completed, and end the reaction. Collect for use.

[0054] Silane polymer 7 (degree of polymerization 3)

[0055] Under nitrogen protection, add 186g of methacryloxypropyltrimethoxysilane, 41g of propyltrimethoxysilane, and 68g of methanol to a three-necked flask, stir well and heat to 45°C, mix 12g of water with 24g of methanol, add 30% hydrochloric acid to adjust the pH to 3, then add to a constant pressure dropping funnel and drip, drip in about 4 hours, keep warm for 0.5 hours after dripping, then heat to 85°C and reflux for 2 hours, then slowly collect alcohol for 5 hours, keep warm for 1 hour after the alcohol collection is completed, and end the reaction. Collect for use.

[0056] Examples and Comparative Examples

[0057] Example 1

[0058] 66 g of isooctyl acrylate, 22.4 g of butyl acrylate, 0.4 g of hydroxybutyl acrylate, and 100 g of ethyl acetate were added to a reactor, the temperature was raised to 65°C, and nitrogen bubbling was performed for 1 hour to replace the reaction system with nitrogen. Then, 0.02 g of benzoyl peroxide as a thermal initiator was added thereto. After the initiation began, a compound of 0.2 g of silane polymer 1 and 19.8 g of ethyl acetate prepared previously was slowly added thereto. The addition time was controlled to be 45 min. After the addition, the reaction was continued for 5 hours to obtain a silane polymer-modified acrylate pressure-sensitive adhesive.

[0059] Example 2

[0060] 70g of isooctyl methacrylate, 25g of butyl methacrylate, 1g of hydroxypropyl acrylate, and 100g of ethyl acetate were added to a reactor, the temperature was raised to 65°C, and nitrogen bubbling was performed for 1 hour to replace the reaction system with nitrogen. Then, 0.01g of azobisisobutyronitrile and 0.01g of benzoyl peroxide as thermal initiators were added thereto. After the initiation began, a compound of 0.2g of silane polymer 2 prepared previously and 19.8g of ethyl acetate was slowly added thereto. The addition time was controlled to be 45min. After the addition, the reaction was continued for 5 hours to obtain a silane polymer-modified acrylate pressure-sensitive adhesive.

[0061] Example 3

[0062] 30g of isooctyl acrylate, 30g of n-octyl acrylate, 10g of butyl acrylate, 2.6g of hydroxybutyl acrylate, and 100g of ethyl acetate were added to a reactor, the temperature was raised to 65°C, and nitrogen bubbling was performed for 1 hour to replace the reaction system with nitrogen. Then 0.02g of azobisisobutyronitrile as a thermal initiator was added thereto. After the initiation began, a compound of 0.2g of silane polymer 3 prepared previously and 19.8g of ethyl acetate was slowly added thereto. The addition time was controlled to 45min. After the addition, the reaction was continued for 5 hours to obtain a silane polymer-modified acrylate pressure-sensitive adhesive.

[0063] Comparative Example 1

[0064] The preparation process of the acrylic pressure-sensitive adhesive is similar to that of Example 1, except that no silane polymer solution is added.

[0065] Comparative Example 2

[0066] The preparation process of the acrylic pressure-sensitive adhesive is similar to that of Example 2, except that the silane polymer 2 is replaced by the functional silane monomer γ-(2,3-epoxypropoxy)propyltrimethoxysilane.

[0067] Comparative Example 3

[0068] The preparation process of the acrylic pressure-sensitive adhesive is similar to that of Example 2, except that the thermal initiator is first reacted for 5 hours to obtain the acrylic pressure-sensitive adhesive, and then the composite of silane polymer 2 and ethyl acetate is added. The specific preparation process is:

[0069] 70g of isooctyl methacrylate, 25g of butyl methacrylate, 1g of hydroxypropyl acrylate, and 100g of ethyl acetate were added to a reactor, the temperature was raised to 65°C, and nitrogen bubbling was performed for 1 hour to replace the reaction system with nitrogen. Then, 0.01g of azobisisobutyronitrile and 0.01g of benzoyl peroxide as thermal initiators were added thereto, and the reaction was continued for 5 hours after the initiation to obtain an acrylate pressure-sensitive adhesive; then, a compound of 0.2g of silane polymer 2 and 19.8g of ethyl acetate was slowly added to the acrylate pressure-sensitive adhesive, the addition time was controlled at 45min, and the mixture was mixed evenly.

[0070] Comparative Example 4

[0071] The preparation process of the silane polymer modified acrylic pressure-sensitive adhesive is similar to that of Example 2, except that the silane polymer 1 is replaced by the silane polymer 4.

[0072] Comparative Example 5

[0073] The preparation process of the silane polymer modified acrylic pressure-sensitive adhesive is similar to that of Example 3, except that silane polymer 3 is replaced by silane polymer 5.

[0074] Comparative Example 6

[0075] The preparation process of the silane polymer modified acrylic pressure-sensitive adhesive is similar to that of Example 3, except that silane polymer 3 is replaced by silane polymer 6.

[0076] Comparative Example 7

[0077] The preparation process of the silane polymer modified acrylic pressure-sensitive adhesive is similar to that of Example 2, except that the silane polymer 2 is replaced by the silane polymer 7.

[0078] Detection test:

[0079] The performance tests were performed on Examples 1-3 and Comparative Examples 1-6. The specific test methods are as follows. The test data are shown in Table 1.

[0080] Peel force test:

[0081] The silane-modified acrylate pressure-sensitive adhesive was coated on the release film with a thickness of 18 um, and then transferred to the polarizer. After aging at 23°C for 3 days, the polarizer was made into 2.54*15 cm strips and attached to the glass plate. The strips were roller-bonded and kept at 23°C and 50% relative humidity (RH) for 2 hours. The 180° peel strength at a peel speed of 300 mm / min was measured using a tensile testing machine (manufactured by Kejian Instrument, KJ-1065A) in accordance with the national standard GB / T2792-2014.

[0082] Weathering test:

[0083] In a clean room, the acrylic pressure-sensitive adhesive in the embodiment and the comparative example was first coated on a release film with a thickness of 18 μm, and then transferred to a polarizer; the polarizer was cut into strips with a width of 100 mm and a length of 210 mm, and then the strips were attached to a glass plate at a pressure of 5 kg / cm 2 The sample was bonded to the glass plate with a pressure of 100°C, and then degassed at 50°C / 0.5MPa for 20 minutes to obtain a sample without bubbles or foreign matter. 85℃ / 85%Relative humidity (RH ) (Abbreviated as Double 85) Observe regularly under high temperature and high humidity conditions.

[0084] When the double 85 aging is performed for 250 hours and 500 hours, if there is no abnormality on the surface of the polarizer or 1-3 bubbles appear or the acrylic pressure-sensitive tape appears to be drawing, put the sample back to the double 85 aging environment to continue the weather resistance test and record the phenomenon; if the acrylic pressure-sensitive tape appears to be warped, do not put the sample back to the double 85 aging environment.

[0085] Table 1 Test data of various properties of Examples 1-3 and Comparative Examples 1-7

[0086]

[0087] in conclusion:

[0088] Comparative Example 1 did not add silane polymer, resulting in a very high initial peel force of the acrylic pressure-sensitive adhesive. When the peel force was tested, the polarizer broke due to the excessive adhesion. When the weather resistance test was conducted, due to the high temperature and high humidity conditions and the fact that the substances therein had no effect on the glass, warping occurred in the early stages.

[0089] In Comparative Example 2, only functional silane monomer was added. During aging, the peeling force increased rapidly and then decayed. Bubbles and warping occurred during the weather resistance test.

[0090] In Comparative Example 3, the silane polymer was added after the copolymerization of the acrylic pressure-sensitive adhesive was completed. Since the silane polymer reacted with the glass but did not react with the glue, it would show drawing and warping phenomena in the later stage of the weather resistance test.

[0091] In Comparative Example 4, the polymerization degree of the silane polymer is too low, and its peeling force increases and decays quickly, and bubbles and warping appear early in the weather resistance test.

[0092] In Comparative Example 5, the polymerization degree of the silane polymer is too high, resulting in a too slow rise in the peeling force. During the weather resistance test, the peeling force on the glass rises slowly, and the polarizer easily shrinks under high temperature and high humidity conditions, which causes it to warp.

[0093] The silane ratio of the silane polymer in Comparative Example 6 is too low, resulting in a slow increase in the peeling force and poor compatibility with the glue, resulting in stringing of the adhesive layer.

[0094] The silane ratio of the silane polymer in Comparative Example 7 is too high, resulting in a rapid increase in peel force and warping of the double 85 adhesive after aging for 500 hours.

[0095] Therefore, the silane polymer requires a suitable silane ratio and degree of polymerization to adjust the appropriate climbing rate and ultimately obtain the appropriate initial peel force and optimal weather resistance.

[0096] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A silane polymer, characterized in that The silane polymer is prepared by hydrolysis and condensation reaction of functional silane monomer and alkoxysilane monomer in solvent 1 at a molar ratio of 2:1 to 1:3 under the action of a catalyst water-alcohol solution; the polymerization degree of the silane polymer is 2-6.

2. The silane polymer according to claim 1, characterized in that The functional silane monomer is one or more of vinyl silane, mercapto silane, acyloxy silane and epoxy silane, and the alkoxy silane monomer is alkyl trialkoxy silane and / or tetraalkoxy silane with different alkyl chain lengths.

3. The silane polymer according to claim 2, characterized in that The functional silane monomer is one or more of vinyl trimethoxysilane, mercaptopropyl trimethoxysilane, methacryloxy trimethoxysilane, Y-(2,3-epoxypropyloxy)propyl trimethoxysilane, and thiocyanatopropyl trimethoxysilane; The alkoxysilane monomer is one or more of methyltrimethoxysilane, methyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, tetramethoxysilane, tetraethoxysilane and tetrapropoxysilane.

4. The silane polymer according to claim 2, characterized in that The catalyst is one or more of hydrochloric acid, nitric acid, sulfuric acid, acetic acid, trifluoromethanesulfonic acid, oxalic acid, and dodecylbenzenesulfonic acid; The first solvent is one or more of methanol, ethanol, isopropanol, pentanol and octanol.

5. A method for preparing a silane polymer, characterized in that: The steps include: S1: adding a catalyst to a hydroalcoholic solution and adjusting the pH to acidic to obtain a catalyst hydroalcoholic solution; S2: under nitrogen protection, functional silane monomer, alkoxysilane monomer and solvent are added into the reactor in proportion and mixed, and the oil bath is heated; S3: adding the catalyst aqueous alcohol solution obtained in step S1 dropwise into the reactor to carry out a hydrolysis condensation reaction to obtain a silane polymer.

6. The method for preparing a silane polymer according to claim 5, characterized in that: In step S1, the weight ratio of water to alcohol is 1:1-1:3, and the pH value of the catalyst aqueous alcohol solution is 2-6; In terms of weight, the amount of solvent 1 added in step S2 is 0.3-2 times the total amount of the material, and the oil bath is heated to 40-50°C: After the catalyst aqueous alcohol solution is added dropwise in step S3, the temperature is first kept warm and then slowly raised to 75-110° C.; the solvent is removed while the hydrolysis condensation reaction is carried out; The amount of the catalyst aqueous alcohol solution added in step S3 is such that the degree of polymerization of the silane polymer is 2-6.

7. A silane polymer modified acrylate pressure-sensitive adhesive, characterized in that: The silane polymer modified acrylate pressure-sensitive adhesive is obtained by adding silane polymer to the (meth)acrylate monomer and (meth)acrylic acid functional monomer in solvent 2 after being initiated by a thermal initiator, and then reacting.

8. The silane polymer modified acrylate pressure-sensitive adhesive according to claim 7, characterized in that: The (meth)acrylate monomer is a (meth)acrylate alkyl ester containing 1 to 12 carbon atoms; the (meth)acrylic acid functional monomer is a monomer containing a hydroxyl functional group or a carboxyl functional group that reacts with a silane polymer.

9. A method for preparing a silane polymer modified acrylic pressure-sensitive adhesive, comprising the following steps: Add (meth)acrylate monomer, (meth)acrylic acid functional monomer and solvent 2 into a reaction kettle, heat to 55-75°C, add a thermal initiator, and after initiation, slowly add a silane polymer solution, control the addition time to 30-60 minutes, and continue to react after addition to obtain a silane polymer modified acrylate pressure-sensitive adhesive.

10. Use of the silane polymer modified acrylate pressure-sensitive adhesive according to any one of claims 7 to 8 in 3C electronic product screens.

Citation Information

Patent Citations

  • Fluorine-silicon modified hydroxy acrylic resin and preparation method thereof

    CN102746449A

  • Composite particles and a process for making the same

    CN105492521A

  • Damp heat-resistant light-cured pressure-sensitive adhesive and preparation method thereof

    CN106147624A

  • Preparation method of amine pressure-sensitive microcapsule curing agent

    CN116023630A

  • Organic silicon modified polyacrylate pressure-sensitive adhesive and preparation method thereof

    CN118374262A